OPTIMIZATION ANALYSIS OF WOOD TRANSPORTATION COST USING STEPPING STONE METHOD - Henri Pandiangan (Jurnal Mantik Penusa, 2017)
Implementation is an action or implementation of a plan that has been prepared carefully and in detail. Implementation is usually done after planning has been considered a fix. Cost optimization is an effort made to obtain a better final result, or it can be an attempt to obtain a smaller expenditure / effort to minimize expenses and obtain maximum profits. Method of transportation or often called stepping stone is the method used to manage distribution from sources that provide the same products in places that need them optimally. The allocation of these products must be arranged in such a way because there are differences in transportation costs (allocations) from one source to several different destinations - and from several sources to a different destination